Proceedings of the ACM SIGCOMM '97 Conference on Applications, Technologies, Architectures, and Protocols for Computer Communic 1997
DOI: 10.1145/263105.263151
|View full text |Cite
|
Sign up to set email alerts
|

Internet routing instability

Abstract: This paper examines the network inter-domain routing information exchanged between backbone service providers at the major U.S. public Internet exchange points. Internet routing instability, or the rapid fluctuation of network reachability information, is an important problem currently facing the Internet engineering community. High levels of network instability can lead to packet loss, increased network latency and time to convergence. At the extreme, high levels of routing instability have lead to the loss o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
0
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 236 publications
(78 citation statements)
references
References 7 publications
3
74
0
1
Order By: Relevance
“…The effectiveness of TERCs depends on the Internet routing stability during the connection lifetime of an HTTP session. Our measurements (see Section V-B-4) and results by others [30], [24] suggest that for the short duration of an HTTP connection, routing is mostly stable.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…The effectiveness of TERCs depends on the Internet routing stability during the connection lifetime of an HTTP session. Our measurements (see Section V-B-4) and results by others [30], [24] suggest that for the short duration of an HTTP connection, routing is mostly stable.…”
Section: Introductionsupporting
confidence: 62%
“…By placing caches [30] suggest that most routes remain stable over the small lifetime of an HTTP connection. Labovitz et al [24] studied Border Gateway Protocol (BGP) route changes and concluded, similarly, that in reality, Internet routing is stable. They found that 80% of the routes change at a frequency lower than once a day.…”
Section: ) Stabilitymentioning
confidence: 92%
“…A similar argument can be made in the case of [10], where lookups are accelerated using memory placement and pipelining. Some protocol-based solutions have emerged ( [5], [6], [4], [7], [8], [9]), but all of these demand modifications to the current Internet Protocol and raise the complexity of routing without completely avoiding the prefix matching problem.…”
Section: A Related Researchmentioning
confidence: 99%
“…When the message loss probability is very low or uncommon, they can give a very high degree of reliability. But, failure scenarios such as router overload and system-wide noise which are known to be common in Internet protocols can cause these protocols to behave pathologically [15,25].…”
Section: Introductionmentioning
confidence: 99%